2017
DOI: 10.1590/0102-311x00206516
|View full text |Cite
|
Sign up to set email alerts
|

Quanto custa o atraso na concessão de patentes de medicamentos para a saúde no Brasil?

Abstract: The backlog in processing patent applications in Brazil has persisted since the enactment of Law 9,279/1996, when the country resumed granting patents on drugs. The agencies responsible for granting such patents, namely the Brazilian National Patent and Trademark Office (INPI) and the Brazilian National Health Surveillance Agency (Anvisa) cite technical and administrative reasons for the backlog. However, little research has focused on the economic impacts for health due to the inefficiency of the Brazilian pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…Thus, if an application took 13 years to be examined and the patent was granted, it would gain another 10 years of validity, adding up to 23 years of monopoly for its holder. Jannuzzi and Vasconcellos (2017) indicated that this extension should be exceptional, but it has become commonplace, occurring for practically 100% of the patents granted for medicines after 1992-mostly filed by foreign companies. In this study, it was discovered that even after the request to prioritize examination by the MS, 76.5% of the regular patents granted had their monopoly period extended.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if an application took 13 years to be examined and the patent was granted, it would gain another 10 years of validity, adding up to 23 years of monopoly for its holder. Jannuzzi and Vasconcellos (2017) indicated that this extension should be exceptional, but it has become commonplace, occurring for practically 100% of the patents granted for medicines after 1992-mostly filed by foreign companies. In this study, it was discovered that even after the request to prioritize examination by the MS, 76.5% of the regular patents granted had their monopoly period extended.…”
Section: Discussionmentioning
confidence: 99%
“…As farmacêuticas nacionais, embora invistam aproximadamente 5% do faturamento em P&D, que é uma taxa superior à média da indústria brasileira, ainda apresentam uma destinação baixa de recursos em comparação ao que ocorre no mundo, com taxa superior a 17% do total de vendas 44 . O resultado desse baixo investimento se reflete no déficit da balança comercial e no baixo número de patentes, que representava, em 2015, somente 0,06% das patentes farmacêuticas mundiais 45 . Para a indústria farmacêutica, a patente é o principal instrumento de apropriação de resultados da inovação.…”
Section: Figuraunclassified
“…Quanto ao atraso na concessão de patentes farmacêuticas, o gargalo encontra-se no âmbito técnico-administrativo. No INPI, não há examinadores e infraestrutura suficientes para análise e tramitação dos processos administrativos, e o conflito de competência técnica entre o INPI e a Anvisa levou, durante muito tempo, a uma duplicidade na análise, o que só foi superado com a assinatura da Portaria Conjunta n o 1, de 12 de abril de 2017 45 .…”
Section: Figuraunclassified
“…No primeiro estudo, realizado em 2016, a análise potencial de custo adicional para o SUS, relativo a nove medicamentos com patentes com prazo estendido, era de R$ 2,1 bilhões 19 . No segundo estudo 20 , indicou-se um custo adicional potencial de R$ 288,4 milhões para três medicamentos antirretrovirais.…”
Section: Incluídounclassified